The First Brazilian Symposium on Computer Music presents Brazilian computer music potentials - Caxambu, MG, 1994 - Loureiro, Mauricio (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2019.10463, 2019)
The main objective of this talk is to report on the First Brazilian Symposium on Computer Music, which occurred in August 1994, at the city of Caxambu, Minas Gerais, promoted by the UFMG. The meeting occurred one year after the creation of NUCOM, a group of young academics dedicated to this emerging research field in Brazil gathered as a discussion list. This quite exciting and fancy event at Hotel Gloria in Caxambu was able to imposingly launch the group to the national, as well as to the international academic community. First, due to the excellency of the event’s output and its daring program, that included 34 selected papers by researchers from various institutions from Argentina, Brazil, Canada, Denmark, France, Hong Kong, Mexico, UK, and USA, five lectures an two panels of discussion offered by researchers from the most advanced computer music research centers all over the world. The program also included eight concerts, two of them featuring traditional music, such as Bach, Mozart, and Brazilian music.Six computer music concerts presented 48 selected compositions submitted to the symposium. Second, as the symposium happened as apart of the 14th Congress of Brazilian Computer Science Society (SBC), the excellency of its output was able to attract the interest of SBC’s board of directors. They invited NUCOM to integrate the society as a Special Committee, which are sub-groups of SBC dedicated to specific computer science topics. At the end of the description, this report aims at raising questions, arguments, and debates about today’s format of NUCOM meetings, considering more seriously the interdisciplinary character of the methodologic approaches adopted by the field. Interdisciplinarity should be pursued by striving to contaminate a growing number of different topics of musical sciences, as well as of other research fields.